THE ROLE OF MICROORGANISM IMMOBILIZATION IN THE BIOTECHNOLOGY OF NITROGEN COMPOUND REMOVAL Hrynevych A.O., Sabliy L.A. - Hrynevych A.O.; Sabliy L.A. (Biotechnologia Acta)
In recent years, technologies employing immobilized microorganisms have demonstrated significant potential for improving wastewater treatment methods, offering substantial advantages.